Pengaruh Investasi, Inflasi dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Yuni Maulida; Abdul Hamid; Faisal Umardani Hasibuan (JIM: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to determine the effect of investment, inflation and human development index on economic growth in Aceh Province. The research method used is a quantitative method using secondary data from 2006-2020. Data analysis used multiple linear regression equation, t test, F test and coefficient of determination test (R2). The results of the multiple linear regression equation test show that investment has a negative effect on economic growth, inflation and the human development index have a positive effect on economic growth. The results of the t-test of the investment variable t sig > 5% (0.0213 > 0.05) can be stated that investment has a not significant effect on economic growth, the inflation variable t sig > 5% (0.484 > 0.05) can be stated that inflation has a not significant effect on economic growth . The human development index variable t sig < 5% (0.001 <0.05) can be stated that the human development index has a significant effect on economic growth. The results of the F F test sig < 5% (0.023 <0.05) can be stated simultaneously that investment, inflation and human development index have a significant effect on economic growth in Aceh Province. The test results of the coefficient of determination (R2) obtained 0.895 or 89.5% investment, inflation and human development index can explain the variable economic growth.